Answer:
x=3
Step-by-step explanation:
You have to multiply exponents.
Answer:
D.
Step-by-step explanation:
To find the equation of g(x), we can substitute the point into each of the equations.
A. g(x) = (1/4x)^2
1 = (1/4 * 2)^2
1 = (1/2)^2
1 = 1/4
This statement is false, so this is not the equation.
B. g(x) = 1/2 * x^2
1 = 1/2 * (2)^2
1 = 1/2 * 4
1 = 2
This statement is false, so this is not the equation.
C. g(x) = 2x^2
1 = 2 * 2^2
1 = 2 * 4
1 = 8
This statement is false, so this is not the equation.
D. g(x) = (1/2x)^2.
1 = (1/2 * 2)^2
1 = 1^2
1 = 1
This statement is true, so this is your answer.
Hope this helps!
Answer:
D: 3(x + 5)(x + 5)
Step-by-step explanation:
Try multiplying the last answer choice (D); the result is 3(x^2 + 10x + 25), or
3(x + 5)(x + 5).